Health needs: policy plan and school practice in Greece - Soultatou, Pelagia; Duncan, Peter; Athanasiou, Kyriacos; Papadopoulos, Irena (Health Education, 2011)
Purpose – The purpose of this paper is to explore the concept of health-related needs on a policy design and curriculum enactment basis in terms of the national school health education curriculum in Greek secondary education. Design/methodology/approach – A single case study, using an ethnographic approach, was conducted in Greece, seeking to understand the continuum from policy design to curriculum enactment in respect of health-related needs. Three sources of data were used to meet this goal: policy texts, observation, and interviews. Multilevel sampling was employed to select one secondary school as a site for “good practice”. Grounded theory coding, thematic analysis and critical discourse analysis identified themes associated with the idea of health-related through the corpus of data. Findings – On a policy plan level the concept of health-related needs was coupled with and reduced to a predetermined list of health-related subjects; and the list of health-related topics had not been updated for long and was characterised by a rather biomedical orientation. On a school practice level the stage of needs assessment was not applied, the list of health-related subjects advocated in the policy plan was used on a proactive, normative and top down basis, and the students' felt needs tended to be disregarded. Originality/value – This study followed up the continuum from policy design to school practice regarding the concept and practice of health needs, highlighting the possibilities and the problems from both perspectives.